A Comparative Study of the Rooot forming Effect of Indole Propionic Acid (IPA), Indole Butyric Acid (IBA) and Naphthalene Acetic Acid (NAA) on the Stem Cuttings of Dalbergia sisso Roxb. - Pain, S. K.; Roy, Bidyut Kumar (Indian Forester, 1981)
The effect of quick dip method of application of 1000 ppm IPA, IBA and NAA was studied in respect of formation of roots in the stem cuttings of Dalbargia sisso Roxb. during summer, and in case or IPA with 500 and 1000 ppm of IPA during the winter were studied. In the summer planted stem cuttings the best results were obtained with IBA (100%), next in NAA (80%), then in IPA (60%) and least in the control (20%). In the winter planted cuttings, 100% rooting was noted with 1000 ppm IPA and 80% with 500 ppm IPA. The results obtained have been discussed.